Effect of a global alteration of running technique on kinematics and economy - Dallam, G. M.; Wilber, R. L.; Jadelis, K.; Fletcher, G.; Romanov, N. (Journal of Sports Sciences, 2005)
In this study, we examined the consequences of a global alteration in running technique on running kinematics and running economy in triathletes. Sixteen sub-elite triathletes were pre and post tested for running economy and running kinematics at 215 and 250m·min-1. The members of the treatment group (n=8) were exposed to 12 weeks of instruction in the "pose method" of running, while the members of the control group (n=8) maintained their usual running technique. After the treatment period, the experimental group demonstrated a significant decrease in mean stride length (from 137.25±7.63cm to 129.19±?7.43cm; P <?0.05), a post-treatment difference in vertical oscillation compared with the control group (6.92±?1.00 vs. 8.44±1.00cm; P ?<0.05) and a mean increase in submaximal absolute oxygen cost (from 3.28±0.36l·min-1 to 3.53±?0.43l·min-1; P <0.01). The control group exhibited no significant changes in either running kinematics or oxygen cost. The global change in running mechanics associated with 12 weeks of instruction in the pose method resulted in a decrease in stride length, a reduced vertical oscillation in comparison with the control group and a decrease of running economy in triathletes.